EXPLORING CONSTRUCTED VISUAL REPRESENTATIONS OF SELF: A SEMIOTIC ANALYSIS OF INSTAGRAM AND FACEBOOK SELFIES - Tandi, Yuzril Reynaldi; Mahmud, Murni (Journal of English Literature and Linguistic Studies, 2025)
This research is a study on "Exploring Visual Representations of the Constructed Self: A Semiotic Analysis of Instagram and Facebook Selfies". This research has two objectives, namely to find out the differences in selfie photos between male and female as well as the visual representations formed from each selfie photo pose that has been selected for research and what is the reason for someone to take a selfie. This research uses a qualitative semiotic research method. The data that was taken in the form of photos of public figures from social media Facebook and Instagram. The sampling method to collect the data was purposive sampling. This method is useful for filtering every selfie photo from the public that used, namely the duckface pose, outstretched arm, tiltle of head, eye squint, and peace. Based on the results of the analysis, selfies taken by males and females tend to have differences. The difference in general is that males tend to judge themselves based on their own thoughts. Whereas female tend to judge themselves based on the views of others, people take selfies for many reasons. One of the most common reasons is to capture a moment or memory with themselves in it.